2008
DOI: 10.3747/co.v15i2.238
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicine and Biomodulation in Cancer Patients—Part Two

Abstract: Traditional Chinese Medicine (TCM) is a whole system containing therapeutic interventions that individually induce biomodulation at the physiologic, chemical, and molecular levels. The theory of TCM proposes a synergy between specific interventions selected as part of a care plan based on TCM diagnostic theory. Combining TCM with the modern practice of oncology seems, in conjunction with biomedical interventions (surgery, radiotherapy, chemotherapy, and pharmaceuticals), to have potential advantages through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 213 publications
(244 reference statements)
0
6
0
Order By: Relevance
“…The literature review also provided scientific evidence of the multiple therapeutic benefits associated with diverse mind-body, bioenergetic, body-manipulative, and biologically based healing practices 10,11,43,70,94,95 . Although the research studies are of varying methodologic rigour, and future work to establish dose, frequency, and duration of treatment effects is needed, consensus concerning the relevance of those techniques in mainstream practice is converging.…”
Section: Scientific Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The literature review also provided scientific evidence of the multiple therapeutic benefits associated with diverse mind-body, bioenergetic, body-manipulative, and biologically based healing practices 10,11,43,70,94,95 . Although the research studies are of varying methodologic rigour, and future work to establish dose, frequency, and duration of treatment effects is needed, consensus concerning the relevance of those techniques in mainstream practice is converging.…”
Section: Scientific Evidencementioning
confidence: 99%
“…Typically, that treatment involves standard chemotherapies, surgical and radiation oncology procedures, biomarker-driven treatment, and healing therapies. Healing therapies are selected from mind-body, manipulative, and body-, energy-, and biologically-based practices 41,62,70,86,94,95 . An integrative approach applies evidenced-based, multimodal, multi-targeted therapies with synergistic effects to intended targets.…”
Section: Clinical Approachmentioning
confidence: 99%
“…The remedies used in homeopathy are controversial, but some merit may lie in the therapeutic relationship and the non-specific effects of the homeopathic system 4 . Chinese medicine has been particularly fruitful 5,6 . One of the components of Chinese medicine is acupuncture, which has already been shown to be a useful modality for symptom control.…”
Section: Increased Research Opportunitiesmentioning
confidence: 99%
“…In preclinical studies, researchers found that the PHY906 combination of Chinese herbs enhances the antitumour activity of conventional chemotherapy with capecitabine, irinotecan, or 5-fluorouracil, by enhancing the cytotoxic effects of those agents. Phytoceutica is currently conducting phase I and II studies in colorectal, hepatocellular, and pancreatic cancers 5,6 .…”
Section: S62mentioning
confidence: 99%
“…7 New evidence suggests that radiation may expose tumor antigen and, together with immune-enhancing adjuvants, can function as a vaccine. Many Asian herbs display immune-enhancing activities 8 and could result in both a beneficial local effect as well as an abscopal effect when combined with radiotherapy. 9 Unfortunately, our methodology for evaluating therapeutic gain in humans with cancer is limited, but new functional imaging techniques using SPECT (single photon emission computed tomography) and PET nuclear medicine scans or nuclear magnetic resonance are promising.…”
Section: The Concept Of Therapeutic Gainmentioning
confidence: 99%